Characterisation of fungicidal and non-fungicidal effects of Inatreq™ active - Bagley, Stuart (2021)
With growing demand for increased crop yields, mitigating losses due to abiotic and biotic stresses is of paramount importance. A new fungicide with a novel mode of action effective in wheat against the pathogen responsible for Septoria tritici blotch (Zymoseptoria tritici), has recently been released by Corteva Agriscience. Inatreq™ active (active ingredient fenpicoxamid) is the first commercially available picolinamide fungicide. Preliminary observations of this fungicide suggest that it may also have biostimulant-like properties, unrelated to its fungicidal activity. The aim of this study is to further characterise the fungicidal activity of Inatreq when applied as a curative application, using traditional and image-based assessment techniques. This work also aims to characterise the beneficial non-fungicidal effects associated with the application of Inatreq, and to begin to understand the mechanisms underlying this activity.